Original paperPredictors of distant metastasis after combined HDR brachytherapy and external beam radiation for prostate cancer - Kamrava, Mitchell; Rwigema, Jean-Claude; Chung, Melody; Banerjee, Robyn; Wang, Jason; Steinberg, Michael; Demanes, David Jeffrey (Journal of Contemporary Brachytherapy, 2013)
Purpose : To determine predictors of distant metastases (DM) in prostate cancer patients treated with high dose rate brachytherapy boost (HDR-B) and external beam radiation therapy (EBRT). Material and methods: From 1991 to 2002, 768 men with localized prostate cancer were treated with HDR-B and EBRT. The mean EBRT dose was 37.5 Gy (range: 30.6-45 Gy), and the HDR-B was 22 or 24 Gy delivered in 4 fractions. Univariate and multivariate analyses using a Cox proportional hazards model including age at diagnosis, T stage, Gleason score (GS), pretreatment PSA, biologically equivalent dose (BED), and use of androgen deprivation therapy (ADT) was used to determine predictors of developing distant metastases. Results: The median follow-up time for the entire patient population was 4.2 years (range: 1-11.2 years). Distant metastases were identified in 22/768 (3%) of patients at a median of 4.1 years. PSA failure according to the Phoenix definition developed in 3%, 5%, and 14% of men with low, intermediate, and high risk disease with a median time to failure of 3.8 years. Prostate cancer specific mortality was observed in 2% of cases. T stage, GS, and use of ADT were significantly associated with developing DM on univariate analysis. GS, and use of ADT were the only factors significantly associated with developing DM on multivariate analysis (p < 0.01). Patients who received ADT had significantly higher risk features suggesting patient selection bias for higher DM in this group of patients rather than a negative interaction between HDR-B and EBRT. Conclusions : In men treated with HDR-B and EBRT, GS is a significant factor on multivariate analysis for developing distant metastasis.